Molecular Characterization of an SV Capture Site in the Mid-Region of the Presynaptic CaV2.1 Calcium Channel C-Terminal - Snidal, Christine A.; Li, Qi; Elliott, Brittany B.; Mah, Henry K.-H.; Chen, Robert H. C.; Gardezi, Sabiha R.; Stanley, Elise F. (Frontiers in Cellular Neuroscience, 2018)
Neurotransmitter is released from presynaptic nerve terminals at fast-transmitting synapses by the action potential-gating of voltage dependent calcium channels (CaV), primarily of the CaV2.1 and CaV2.2 types. Entering Ca2+ diffuses to a nearby calcium sensor associated with a docked synaptic vesicle (SV) and initiates its fusion and discharge. Our previous findings that single CaVs can gate SV fusion argued for one or more tethers linking CaVs to docked SVs, but the molecular nature of these tether have not been established. We recently developed a cell-free, in vitro biochemical assay, termed SV pull-down (SV-PD), to test for SV binding proteins and used this to demonstrate that CaV2.2 or the distal third of its C-terminal can capture SVs. In subsequent reports we identified the binding site and characterized an SV binding motif. In this study, we set out to test if a similar SV-binding mechanism exists in the primary presynaptic channel type, CaV2.1. We cloned the chick variant of this channel and to our surprise found that it lacked the terminal third of the C-terminal, ruling out direct correlation with CaV2.2. We used SV-PD to identify an SV binding site in the distal half of the CaV2.1 C-terminal, a region that corresponds to the central third of the CaV2.2 C-terminal. Mutant fusion proteins combined with motif-blocking peptide strategies identified two domains that could account for SV binding; one in an alternatively spliced region (E44) and a second more distal site. Our findings provide a molecular basis for CaV2.1 SV binding that can account for recent evidence of C-terminal-dependent transmitter release modulation and that may contribute to SV tethering within the CaV2.1 single channel Ca2+ domain.